2019
DOI: 10.1186/s12967-019-2046-5
|View full text |Cite
|
Sign up to set email alerts
|

Selective improvement by rifaximin of changes in the immunophenotype in patients who improve minimal hepatic encephalopathy

Abstract: Background Minimal hepatic encephalopathy (MHE) in cirrhotic patients is associated with specific changes in parameters of the immune system reflecting a more pro-inflammatory environment than in patients without MHE. The aims of this work were to assess the effects of rifaximin treatment of cirrhotic patients with MHE on: (1) MHE; (2) intermediate (CD14 ++ CD16 + ) pro-inflammatory monocytes; (3) expression of early activation marker CD69 in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 37 publications
0
20
0
1
Order By: Relevance
“…Using the PHES, 12% of NAFLD patients (7 out of 59) were classified as having MCI. This prevalence is lower than in cirrhotic patients, who show MHE prevalence of 31-59% when diagnosed using the PHES [13,21,30,31]. However, it has been reported that the PHES is not sensitive enough and fails to detect the presence of mild cognitive impairment in a substantial proportion of cirrhotic patients.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Using the PHES, 12% of NAFLD patients (7 out of 59) were classified as having MCI. This prevalence is lower than in cirrhotic patients, who show MHE prevalence of 31-59% when diagnosed using the PHES [13,21,30,31]. However, it has been reported that the PHES is not sensitive enough and fails to detect the presence of mild cognitive impairment in a substantial proportion of cirrhotic patients.…”
Section: Discussionmentioning
confidence: 89%
“…MHE reduces the ability to perform daily life tasks and is associated with altered postural control, increased risk of falls, fractures, and hospitalizations, and of progression to overt hepatic encephalopathy, increased costs, and reduced life quality and span [6,[10][11][12]. Early MHE detection may help to reverse or halt progression of MHE [13].…”
Section: Introductionmentioning
confidence: 99%
“…Rifaximin is a non-absorbable antibiotic that was approved as treatment for the prevention of HE in the USA in 2010 [59]. Rifaximin reduces the risk of overt HE recurrence and mortality [59] and also improves cognitive and motor function in a large percentage of cirrhotic patients with MHE [23].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with rifaximin, a nonpermeable antibiotic, improves cognitive and motor function in a relevant proportion of patients with MHE [22,23], and this is associated with normalization of peripheral IL-17, CCL20, CX3CL1, and IL-15 [23], which promote the infiltration of lymphocytes into the brain. This, together with the above reports, suggests that rifaximin could improve MHE by reducing T lymphocytes infiltration into the brain.…”
Section: Introductionmentioning
confidence: 99%
“…It is postulated that it can regulate the metabolism of intestinal bacteria or stabilize intestinal barrier functions ( Kaji et al, 2017 ; Montagnese et al, 2018 ).Other studies have shown that it has immunomodulatory effects as it reduces inflammation by regulating bacteria. Rifaxmin was shown to improve the immune system in 59% of MHE patients ( Mangas-Losada et al, 2019 ).…”
Section: Effects Of Clinical Treatment On the Intestinal Metabolome Imentioning
confidence: 99%